Study protocol for the safety and efficacy of probiotic therapy on days alive and out of hospital in adult ICU patients: the multicentre, randomised, placebo-controlled Restoration Of gut microflora in Critical Illness Trial (ROCIT). Issue 6 (21st June 2020) - Litton, Edward; Anstey, Matthew; Broadhurst, David; Chapman, Andy R; Currie, Andrew; Ferrier, Janet; Gummer, Joel; Higgins, Alisa; Lim, Jolene; Manning, Laurens; Myers, Erina; Orr, Katrina; et al.
Abstract : Introduction: The effect of early and sustained administration of daily probiotic therapy on patients admitted to the intensive care unit (ICU) remains uncertain. Methods and analysis: The Restoration Of gut microflora in Critical Illness Trial (ROCIT) study is a multicentre, randomised, placebo-controlled, parallel-group, two-sided superiority trial that will enrol 220 patients in five ICUs. Adult patients who are within 48 hours of admission to an ICU and are expected to require intensive care beyond the next calendar day will be randomised in a 1:1 ratio to receive early and sustained Lactobacillus plantarum 299v probiotic therapy in addition to usual care or placebo in addition to usual care. The primary endpoint is days alive and out of hospital to day 60. Ethics and dissemination: ROCIT has been approved by the South Metropolitan Health Service Human Research Ethics Committee (ref: RGS00000004) and the St John of God Health Care Human Research Ethics Committee (ref: 1183). The trial results will be submitted for publication in a peer-reviewed journal. Trial registration number: Australian and New Zealand Clinical Trials Registry (ANZCTR12617000783325); Pre-results.